THE EFFECT OF RED DRAGON FRUIT PEEL EXTRACT (HYLOCEREUS POLYRHIZUS) ON COLLAGEN DEPOSITION IN THE KIDNEYS OF MENOPAUSAL MODEL RATS (RATTUS NORVEGICUS) - Zahra, Fahdia Fitrianti; Sugiritama, I Wayan (E-Jurnal Medika Udayana; Vol 13 No 9 (2024): E-Jurnal Medika Udayana, 2024)
Background: The estrogen hormone possesses nephroprotective properties during menopause that can influence kidney function. This increases collagen deposition in the kidneys. Estrogen deficiency during menopause can be replaced by phytoestrogens. The skin of red dragon fruit ( Hylocereus polyrhizus ) contains numerous anthocyanin contents, which have been proven to exhibit activities as phytoestrogens. Objective: To determine whether there are changes in collagen deposition in the kidneys of menopausal rat models with the administration of Hylocereus polyrhizus peel extract. Methods: This research utilized a randomized post-test control group design with three sample groups that had undergone ovariectomy. The three groups consist a control group without intervention (P0), an intervention group with red dragon fruit peel extract at a dose of 60mg/200gBW (P1), and an intervention group with red dragon fruit peel extract at a dose of 90mg/200gBW (P2). Results: The mean percentage of collagen expression in menopausal rat kidneys in groups P0, P1, and P2 were 0.876 ± 0.433, 0.189 ± 0.102, and 0.162 ± 0.108, respectively. The Kruskal-Wallis test revealed a significant difference with a p-value of 0.000. Post-Hoc Mann-Whitney U test found a significant difference between groups P0 and P1 (p = 0.000), as well as groups P0 and P2 (p = 0.000). However, there was no significant difference between P1 and P2 (p = 0.436). Conclusion: The extract of Hylocereus polyrhizus peel has an effect on the collagen deposition in the kidneys of menopausal rat models. The lowest level of collagen deposition in the kidneys was observed in the intervention group with a dose of 90mg/200gBW. Keywords : Hylocereus polyrhizus, collagen, kidney, menopause